Wnt/β-Catenin Signaling Induces Integrin α4β1 in T Cells and Promotes a Progressive Neuroinflammatory Disease in Mice - Sorcini, Daniele; Bruscoli, Stefano; Frammartino, Tiziana; Cimino, Monica; Mazzon, Emanuela; Galuppo, Maria; Bramanti, Placido; Al-Banchaabouchi, Mumna; Farley, Dominika; Ermakova, Olga; Britanova, Olga; Izraelson, Mark; et al. (The Journal of immunology, 2017)
The mechanisms leading to autoimmune and inflammatory diseases in the CNS have not been elucidated. The environmental triggers of the aberrant presence of CD4+ T cells in the CNS are not known. In this article, we report that abnormal β-catenin expression in T cells drives a fatal neuroinflammatory disease in mice that is characterized by CNS infiltration of T cells, glial activation, and progressive loss of motor function. We show that enhanced β-catenin expression in T cells leads to aberrant and Th1-biased T cell activation, enhanced expression of integrin α4β1, and infiltration of activated T cells into the spinal cord, without affecting regulatory T cell function. Importantly, expression of β-catenin in mature naive T cells was sufficient to drive integrin α4β1 expression and CNS migration, whereas pharmacologic inhibition of integrin α4β1 reduced the abnormal T cell presence in the CNS of β-catenin-expressing mice. Together, these results implicate deregulation of the Wnt/β-catenin pathway in CNS inflammation and suggest novel therapeutic strategies for neuroinflammatory disorders.
Keywords: integrin alfa4beta1; myši; Wnt Signaling Pathway; Integrin alpha4beta1; Inflammation; zánět; beta Catenin; Th1 Cells; mícha; nemoci míchy; beta-katenin; Animals; Mice; zvířata; Spinal Cord Diseases; Mice, Knockout; signální dráha Wnt; Th1 buňky; Spinal Cord; myši knockoutované